Understanding Human Anatomy and Pathology : An Evolutionary and Developmental Guide for Medical Students - Diogo, Rui; Noden, Drew M.; Smith, Christopher M.; Molnar, Julia; Boughner, Julia C.; Amorim Barrocas, Claudia Alexandra; Araujo Bruno, Joana; Taylor & Francis (Boca Raton, FL : CRC Press, 2018)
Understanding Human Anatomy and Pathology: An Evolutionary and Developmental Guide for Medical Students provides medical students with a much easier and more comprehensive way to learn and understand human gross anatomy by combining state-of-the-art knowledge about human anatomy, evolution, development, and pathology in one book. The book adds evolutionary, pathological, and developmental information in a way that reduces the difficulty and total time spent learning gross anatomy by making learning more logical and systematic. It also synthesizes data that would normally be available for students only by consulting several books at a time.Anatomical illustrations are carefully selected to follow the style of those seen in human anatomical atlases but are simpler in their overall configuration, making them easier to understand without overwhelming students with visual information. The book's organization is also more versatile than most human anatomy texts so that students can refer to different sections according to their own learning styles.Because it is relatively short in length and easily transportable, students can take this invaluable book anywhere and use it to understand most of the structures they need to learn for any gross anatomy course.
About the Book -- Introduction -- Conserved Features of Vertebrate Embryology -- Causes and Mechanisms of Developmental Pathologies -- A Holistic Approach to Anatomy -- Head and Neck -- Head and Neck Skeletal System -- Head and Neck Neurovascular System -- Head and Neck Muscular System -- A Summary of the Head and Neck Musculoskeletal, Neurovascular, and Other Structures by Region -- Upper Limb -- Upper Limb Skeletal System -- Upper Limb Neurovascular System -- Upper Limb Muscular System -- Lower Limb -- Lower Limb Skeletal System -- Lower Limb Neurovascular System -- Lower Limb Muscular System -- Trunk -- Trunk Skeletal System -- Trunk Neurovascular System -- Trunk Muscular System -- Suggested Readings -- Plates.
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Anatomy; MEDICAL / Pathology; Anatomical Illustrations; Development; Evolution; embryology and developmental biolgy; evolutionary theory; Gross Anatomy; Human Anatomy; morphology; ontogeny and phylogeny; Pathology; Human anatomy; Anatomy, Pathological